2013
DOI: 10.1097/hjh.0b013e32835f7ecf
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic parameters associated with arterial stiffness in older adults with Type 2 diabetes

Abstract: Central obesity in people with Type 2 diabetes was associated with increased arterial stiffness. This association was independent of the conventional factors associated with central obesity and further studies are required to identify the mechanisms involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 40 publications
4
46
1
3
Order By: Relevance
“…Interestingly, inflammatory markers were associated to PWV but not to IMT. A recent study performed in Edinburgh in a similar setting reported that inflammatory markers were not at all correlated to PWV (17) .…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, inflammatory markers were associated to PWV but not to IMT. A recent study performed in Edinburgh in a similar setting reported that inflammatory markers were not at all correlated to PWV (17) .…”
Section: Discussionmentioning
confidence: 91%
“…10,25 Indices of central obesity including WC and WHtR consistently present higher level of correlation with PWV than BMI, a measure of general obesity, in healthy, diabetic and hypertensive subjects. 10 Similarly in our work, we observed a better correlation between measures of central obesity (WC and VFA) rather than general obesity (BMI and BAI) and PWV.…”
Section: Discussionmentioning
confidence: 95%
“…Whether reducing aortic stiffness will be associated with a better prognosis in patients with type 2 diabetes still needs to be demonstrated in future multiple-intervention prospective investigations. Some previous cross-sectional studies (29,30) have suggested that aortic stiffness might be associated with HbA 1c levels; notably, in this study it was possible to establish temporality, so we can speculate that there is causality between HbA 1c levels and aortic stiffness progression/regression, which may be in part mediated by advanced glycation Heart rate at 1st cf-PWV ( Candidate variables to enter the model: age, sex, baseline BMI, change in weight during follow-up, diabetes duration, physical activity, smoking status, dyslipidemia, insulin, statin and aspirin use, arterial hypertension, number of antihypertensive drugs in use, each macro-and microvascular diabetes complication, mean HbA 1c between 1st and 2nd cf-PWV, baseline glomerular filtration rate, SBP and heart rate at 1st cf-PWV measurement and relative changes in SBP and heart rate between 1st and 2nd cf-PWV, and 1st cf-PWV measurement. Table 2, except mean HbA 1c between 1st and 2nd cf-PWV that was categorized at $7.5% (58 mmol/mol).…”
Section: Discussionmentioning
confidence: 99%